2016
DOI: 10.1111/jan.13064
|View full text |Cite
|
Sign up to set email alerts
|

Delivering compassionate care in intensive care units: nurses' perceptions of enablers and barriers

Abstract: The responsibility for 'compassionate' care is a shared one. Nurses need to be cognizant of factors that are enabling or inhibiting their ability to be compassionate. Healthcare leaders have a responsibility to provide structural support (staffing, education and space) that assist nurses to deliver compassionate care and where appropriate cater for nurses needs so that they are better able to be compassionate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 23 publications
(31 reference statements)
5
67
0
9
Order By: Relevance
“…In designing undergraduate and continuing education curricula, it should be considered that it is not merely the amount of knowledge and contact, but also the quality of contact and the level of support and mentoring that can form more positive attitudes (Chan & Cheng, ; McManus et al., ; Miller, ; Page & Islam, ; Seccombe, ). In addition, echoing the results of Brown and Kalaitzidis () and Jones, Winch, Strube, Mitchell, and Henderson (), we should keep in mind that individual attitudes are not the only determinant of compassionate and high‐quality nursing care. Workplace characteristics and organisational structures such as adequate staffing levels and using specialist disability nurses should be also addressed.…”
Section: Relevance To Clinical Practicementioning
confidence: 54%
“…In designing undergraduate and continuing education curricula, it should be considered that it is not merely the amount of knowledge and contact, but also the quality of contact and the level of support and mentoring that can form more positive attitudes (Chan & Cheng, ; McManus et al., ; Miller, ; Page & Islam, ; Seccombe, ). In addition, echoing the results of Brown and Kalaitzidis () and Jones, Winch, Strube, Mitchell, and Henderson (), we should keep in mind that individual attitudes are not the only determinant of compassionate and high‐quality nursing care. Workplace characteristics and organisational structures such as adequate staffing levels and using specialist disability nurses should be also addressed.…”
Section: Relevance To Clinical Practicementioning
confidence: 54%
“…Various interventions and programmes were highlighted in the reviewed literature, including: Compassion Café (Jones et al, ; Winch, Henderson, & Jones, ); modules with principles of compassionate care (Adam & Taylor, ; Adamson & Dewar, ); Leadership in Compassionate Care Programme (Adamson & Dewar, ; Dewar et al, ; MacArthur, Wilkinson, Gray, & Matthews‐Smith, ); the ENGAGE card (Engaged by your senior team; Nurtured by your manager; Glad to come to work; Acknowledged by your senior team; Guided by your manager; and Empowered to improve patient care) and improvement initiatives (Day, ); Enabling Compassionate Care in Practice Programme (Masterson et al, ); Creating Learning Environments for Compassionate Care (Bridges et al, ); Care Makers Programme (Zubairu et al, ); and Compassion in Practice Vision and Strategy (O'Driscoll et al, ). The complete study characteristics are included in Table and data from individual studies are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies reported on programme characteristics that have led to negative outcomes. These included “outside‐the‐workplace” factors such as the stress caused by competing work and family demands (Jones et al, ). Moreover, nurses in the study by O'Driscoll et al (), expressed frustration at being exhorted, through CiPVS, to deliver compassionate care while feeling that they were not treated with compassion themselves.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations